Propionic acid based additive on aerobic stability of total mixed rations and performance of lactating dairy cows - Ribeiro, Ariádna Patricia (2022)
Twelve Holstein cows with average body weight of 612 kg, 178 ± 60 days in milk (mean ± SD) and average daily milk yield of 27 ± 6.5 kg (mean ± SD) were assigned to a switch-back design to evaluate the effect of applying a propionic acid-based additive on total mixed ration (TMR) during the mixture of ingredients, immediately before feeding, on the animal performance. The set of treatments was designed to perform a comparison between two feeding strategies: cows receiving two daily offers of TMR without treatment (Control); and cows receiving a single daily offer of TMR treated with the additive at 2 L/t of as fed matter (Additive). The ration composition was the same for both treatments, with 44.59% corn silage, 6.40% Tifton haylage, 21.11% rehydrated corn grain silage, 9.25% citrus pulp, 16.33% soybean meal and 2.32% mineral-vitamin mix. Cows fed the additive-treated TMR significantly increased daily milk yield in 2.4 kg without significant changes in dry matter intake (DMI), although only a slight non-significant increase was observed for feed efficiency. The contents of total solids, fat and lactose were decreased in the milk of cows fed the treated TMR, although daily yield of these components was greater due to increased milk yield. Milk crude protein content and milk urea nitrogen (MUN) were not altered by feeding strategy. Energy density of milk was similar across treatments, although energy excretion through milk was greater for the cows fed the additive-treated TMR. Somatic cell count (SCC) was significantly higher for the cows when fed the treated TMR. The additive shifted sorting behavior in favor of longer particles of the ration, in relation to the control treatment. Cows receiving a single daily offer of additive-treated TMR spent less time ingesting and more time ruminating, with greater meal size, shorter meal length and decreased daily meal frequency. TMR offering frequency might be reduced, with a 10.2% increase in milk yield, by using propionic acid based additive.